Culture through comparison: Creating audio-visual listening materials for a CLIL course - Iryna Zhyrun (Universidad de La Sabana, 2016)
Authentic listening has become a part of CLIL materials, but it can be difficult to find listening materials that perfectly match the language level, length requirements, content, and cultural context of a course. The difficulty of finding appropriate materials online, financial limitations posed by copyright fees, and necessity to produce intellectual work led to the idea of designing videos specifically for a university level CLIL course. This article presents a brief overview of current approaches to creating CLIL materials, gives rationale for recording of CLIL audio-visual materials, and discusses their challenges. It provides an example of audio-visual materials design for listening comprehension taking into consideration educational and cultural contexts, course content, and language learning outcomes of the program. In addition, it discusses advantages and limitations of created audio-visual materials by contrasting them with authentic materials of similar type found on YouTube. According to a pilot survey, language used in recorded CLIL videos is easier to understand than the language used in YouTube videos. The content of CLIL videos is more related to students' life and they experience more positive emotions while watching them. CLIL videos bridge the gap between the concepts studied and a local culture making the learning more meaningful and enjoyable.   doi: 10.5294/laclil.2016.9.2.5